If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2cos(2x) + sinx = 0 Remove parenthesis around (2x) 2cos * 2x + sinx = 0 Reorder the terms for easier multiplication: 2 * 2cos * x + sinx = 0 Multiply 2 * 2 4cos * x + sinx = 0 Multiply cos * x 4cosx + sinx = 0 Solving 4cosx + insx = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1insx' to each side of the equation. 4cosx + insx + -1insx = 0 + -1insx Combine like terms: insx + -1insx = 0 4cosx + 0 = 0 + -1insx 4cosx = 0 + -1insx Remove the zero: 4cosx = -1insx Divide each side by '4osx'. c = -0.25ino-1 Simplifying c = -0.25ino-1
| x-18= | | Q-60=85 | | 40x^2+36xy+25y^2=52 | | 9(3x-5)+4x-12= | | 4x-2y=13fory | | (6i)/(-2i) | | a=3.14rh | | X^2-30x+1250=0 | | .125=x/(.275-2x) | | (9x-2y)^1/3=x^2 | | 6-4x=3x^2-8x+3 | | -4(12-183x)=7-2(x-3) | | 3/10y=-1 | | 4x-4=8/3 | | 9-6x=3x^2-10x+3 | | B+11=400 | | X-7/2=x-6/7 | | 9-6x=3x-10x+3 | | -8w-9=-4+2w | | 6-4x=7x+-9x+12 | | 3m/4=3/14 | | 3x^2-10x=299/3 | | y=(36-2x)(12+.50x) | | Y/8=7/32 | | Y/8=7/33 | | -2(6q+3)= | | 3/5t=21 | | 2x-15=-60 | | 4(b+0.6)=4.8 | | 5/6x-13=2 | | 5.2b+4.6=7.72 | | 4t^2-25t+28=0 |